Kompetensi Penyuluh Pertanian dan Kinerja Petani dalam Bercocok Tanam Padi Sawah di Kecamatan Baula Kabupaten Kolaka - Nia Tirani; Dasmin Sidu; Salahuddin Salahuddin (Fakultas Pertanian Universitas Halu Oleo, 2021)
This study used quantitative methods. The data collection procesed was carried out by means of surveys and questionnaires, interviews, literature studies, and documentation. The results showed the competency level of agricultural instructors in Kecamatan Baula. The results showed that the competency levels of agricultural instructors in Kecamatan Baula, Kabupaten Kolaka were categorized as good with an average score of 187. So it can be said that the instructors in Kecamatan Baula had good knowledge, attitudes and skills. The competency level of the instructor's knowledge that reaches the level of remembering, understanding, applying, is 7 respondents or 100%. Respondents who reached the analyzing level were 5 respondents or 71.4%, respondents who reached the evaluation level were 4 respondents or 57.1% and none of the extension workers reached the creating level because the extension workers in Kecamatan Baula had not created the latest innovation or technology. In the attitude competence of the instructor, respondents who reached the level of accepting, responding, self-assessment, and organization were 7 respondents or 100%, and those who reached the level of characterization were 3 respondents or 42%. This is because some extension workers are fair in providing assistance to farmers. respondents who have competency skills at the level of perception, readiness, directed reaction, natural reaction, complex reaction, and adaptation are 7 respondents or 100%. and those who reached the level of creativity were 4 respondents or 57.1% this was because some of the extension workers were creative in establishing field schools for women, so that women also had knowledge in cultivating rice fields. The performance of farmers in cultivating lowland rice in Kecamatan Baula which includes productivity, business profits, administrative performance, and operating performance in Kolaka Regency is in the good category with an average score of 171.5%.